Variasi Bahasa Dalam Film Animasi Nussa & Rara Di Youtube - Ulfa Kurnia; Pahrul. R (Sociale : Journal of Social Science, 2026)
This study aims to determine This study aims to determine the description of literacy in the form of language alteration in the Nussa & Rara animated film episode "Learning Honest". This research is a qualitative descriptive. The provision of information is carried out by following and listening and mastering linguistic data in the form of oral information in the broadcast source of the Nussa & Rara Animated Film. The technique is a listening technique, free to engage in conversation and a note-taking technique. The data analysis method used is the agih method and the technical reading agih method. The results of this study show the form of language variation in this animated film consisting of variations from speakers, variations in terms of formality, users and variations in terms of facilities. 1) the variety of language in terms of speakers is colored by the Jakarta dialect, 2) the alteration in terms of formality using standard and relaxed languages, 3) educational registers give a lot of color in the variety of users, and 4) variations in terms of means of using spoken means in the broadcast of this animated film.